Daedalus MASE (mission assessment through simulation exercise): A toolset for analysis of in situ missions and for processing global circulation model outputs in the lower thermosphere-ionosphere - Sarris, Theodore E.; Tourgaidis, Stelios; Pirnaris, Panagiotis; Baloukidis, Dimitris; Papadakis, Konstantinos; Psychalas, Christos; Buchert, Stephan Christoph; Doornbos, Eelco; Clilverd, Mark A.; Verronen, Pekka T.; Malaspina, David; Ahmadi, Narghes; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Daedalus MASE (Mission Assessment through Simulation Exercise) is an open-source package of scientific analysis tools aimed at research in the Lower Thermosphere-Ionosphere (LTI). It was created with the purpose to assess the performance and demonstrate closure of the mission objectives of Daedalus, a mission concept targeting to perform in-situ measurements in the LTI. However, through its successful usage as a mission-simulator toolset, Daedalus MASE has evolved to encompass numerous capabilities related to LTI science and modeling. Inputs are geophysical observables in the LTI, which can be obtained either through in-situ measurements from spacecraft and rockets, or through Global Circulation Models (GCM). These include ion, neutral and electron densities, ion and neutral composition, ion, electron and neutral temperatures, ion drifts, neutral winds, electric field, and magnetic field. In the examples presented, these geophysical observables are obtained through NCAR’s Thermosphere-Ionosphere-Electrodynamics General Circulation Model. Capabilities of Daedalus MASE include: (1) Calculations of products that are derived from the above geophysical observables, such as Joule heating, energy transfer rates between species, electrical currents, electrical conductivity, ion-neutral collision frequencies between all combinations of species, as well as height-integrations of derived products. (2) Calculation and cross-comparison of collision frequencies and estimates of the effect of using different models of collision frequencies into derived products. (3) Calculation of the uncertainties of derived products based on the uncertainties of the geophysical observables, due to instrument errors or to uncertainties in measurement techniques. (4) Routines for the along-orbit interpolation within gridded datasets of GCMs. (5) Routines for the calculation of the global coverage of an in situ mission in regions of interest and for various conditions of solar and geomagnetic activity. (6) Calculations of the statistical significance of obtaining the primary and derived products throughout an in situ mission’s lifetime. (7) Routines for the visualization of 3D datasets of GCMs and of measurements along orbit. Daedalus MASE code is accompanied by a set of Jupyter Notebooks, incorporating all required theory, references, codes and plotting in a user-friendly environment. Daedalus MASE is developed and maintained at the Democritus University of Thrace, with key contributions from several partner institutions.